Predição das propriedades ópticas lineares e não lineares de um derivado de base de Schiff via DFT - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The search for organic materials with high non-linearities has increased in recent years for technological applications, such as photonics and ultra-fast optical communications. In this work the density functional theory (DFT) calculation combined with a polarizable continuum model (PCM) were used to study the solvent media effects on the electrical and geometrical behaviors of the Schiff-base derivative, (E)-4-[({4-[(piridin-2-ilmetilideno)amino]fenil}amino)-metil]fenol (EPAF). The linear and nonlinear optics parameters, as the dipole moment, linear polarizability, first and second hyperpolarizabilities were calculated at DFT/B3LYP/6-311+G(d) level, for the EPAF molecule in several solvent media. The dynamic behavior of the Hyper-Rayleigh Scattering (HRS) first hyperpolarizability was studied as function of the electric field frequency. The results presented for HRS first hyperpolarizability suggest that the studied crystal has good nonlinear optical properties. In addition, the gap energy was calculated from the HOMO-LUMO energies difference in several solvent media. The EPAF crystal intermolecular interactions were studied by the Hirshfeld surface analysis. The third-order electric susceptibility of the crystal EPAF was also calculated, indicating the EPAF crystal as a promising candidate for NLO applications in photonic and optoelectronic devices.
Prediction of the linear and nonlinear optical properties of a schiff base Derivatives via DFT
Keywords: Base de Schiff; Susceptibilidade elétrica; Polarizabilidade; Hiperpolarizabilidade; Teoria do funcional de densidade (DFT); Schiff Base; Electric susceptibility; Polarizability; Hyperpolarizability; Density functional theory (DFT); CIENCIAS EXATAS E DA TERRA::QUIMICA